2012
DOI: 10.1111/j.1365-2613.2012.00829.x
|View full text |Cite
|
Sign up to set email alerts
|

Heterotopic mineralization (ossification or calcification) in tendinopathy or following surgical tendon trauma

Abstract: SUMMARYHeterotopic tendon mineralization (ossification or calcification), which may be a feature of tendinopathy or which may develop following surgical trauma (repair or graft harvest), has not received much attention. The purpose of this article is to review the prevalence, mechanisms and consequences of heterotopic tendon mineralization and to identify the gaps in our current understanding. We focus on endochondral heterotopic ossification and draw on knowledge of the mechanisms of this process in other tis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
118
2
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 106 publications
(125 citation statements)
references
References 93 publications
4
118
2
1
Order By: Relevance
“…In human, heterotopic ossification is a substantial medical problem because it is associated with pain and dysfunction (28). In systemic heterotopic ossification, a fibrodysplasia ossificans progressiva-like phenotype (29) and ossification of the posterior longitudinal ligament of the spine (30) are important hereditary diseases, although these ossifications occur only several years after birth.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In human, heterotopic ossification is a substantial medical problem because it is associated with pain and dysfunction (28). In systemic heterotopic ossification, a fibrodysplasia ossificans progressiva-like phenotype (29) and ossification of the posterior longitudinal ligament of the spine (30) are important hereditary diseases, although these ossifications occur only several years after birth.…”
Section: Discussionmentioning
confidence: 99%
“…The upregulation of BMP pathway-related genes in the Achilles tendon of Mkx −/− rats suggests that Mkx regulates the BMP pathway. Mechanical stress affects tendon development before and after birth (40), and excessive mechanical stress can lead to ossification of the tendon (28,41). It is also reported that mechanical strain promotes the differentiation of MSCs into tenocytes in vitro (21,42).…”
Section: Discussionmentioning
confidence: 99%
“…The linear appearance and the location of soft tissue mineralisation in our elephants suggest that the digital flexor tendons are the affected structures. Mineralisation of the deep digital flexor tendon in horses has been observed as a response to chronic injury (Dyson, 2003b), and general mineralisation has been described as a feature of tendinopathy (tendon disease arising from overuse) and following trauma in other species (O’Brien et al, 2012). The magnitude of load experienced by structures may be a factor (especially in OA and remodelling, which both increase with increasing age and therefore presumably body weight), as might the type of loading; e.g., altered locomotion or long periods of standing.…”
Section: Discussionmentioning
confidence: 99%
“…Significance of Dcn and Mkx by IL-1β needs to be further investigated. Tendon mineralization can be found as a result of tendon injuries or a feature of tendinopathy [28, 29]. Previous studies reported that mineralization was found in 14–62% of cases following percutaneous or open repair of the Achilles tendon [30] and is thought to be a cause of pain and tendon weakness [31, 32].…”
Section: Discussionmentioning
confidence: 99%